Comparative expressed sequence hybridization detects recurrent patterns of altered sequence expression in oral squamous cell carcinoma - Janjetovic, Snjezana; Sticht, Carsten; Knöpfle, Karl; Joos, Stefan; Hofele, Christof; Lichter, Peter; Freier, Kolja (Oncology reports, 2010)
Despite its common histology and presentation, oral squamous cell carcinoma (OSCC) is associated with widely varying clinical behaviour and response to therapy. To further elucidate the molecular basis of OSCC, an approach for gene expression analysis termed comparative expressed sequence hybridization (CESH) was used in the present study. This straightforward approach allows the rapid delineation of pathophysiologically interesting candidate chromosome regions by a direct detection of aberrant transcriptional activation. CESH profiling of OSCC specimens led to the identification of several novel chromosomal regions. Increased expression compared to a set of control mucosa specimens was found on 1q22-q23, 3q26.3-qter, 4q31.1-q32, 11q12-q13.2, 14q32, 18q12, 19q13.2-q13.3 and 22q13.1-q13.2. Decreased expression was found on 8p22-p23, 16p12 and 16q23-q24. Using CESH, common patterns of altered sequence expression in different OSCC samples were obtained. While some of these regions overlap with those known to be frequently altered in OSCC on the genomic level, this screen revealed novel chromosome subregions with increased transcriptional activity, which are probably independent of the genomic status of the tumor cells.